Pemanfaatan Media Pembelajaran Berbasis Youtube untuk Meningkatkan Kualitas dan Kreativitas Guru Bahasa Inggris SMK - Hamidah, Fitria Nur; Yanuarmawan, Dion; Sukya, Fadelis (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this community service is to socialize the use and the ways of utilizing YouTube as an effective learning media in English learning. The target audience are the English teachers of State Vocational School 2 Kediri. The method which was used in this community service was the approach method, the implementation method which consisted of the preliminary step, the socialization and audience step and the evaluation step. This activity was carried out through several stages, the first step was the introduction phase of Youtube. The second step is searching for English media through YouTube facilities and learning implementation. The last step was evaluation and motivation. The result of this community service showed that English teachers of State Vocational School 2 Kediri city could take the advantages of YouTube facilities as the effective English learning media and YouTube media was very popular with high-level students especially students of State Vocational School 2 Kediri city.